Surgical Treatment of Metastatic Ovarian Tumors From Extragenital Primary Sites. Issue 4 (1st May 2016) - Sal, Veysel; Demirkiran, Fuat; Topuz, Samet; Kahramanoglu, Ilker; Yalcin, Ibrahim; Bese, Tugan; Sozen, Hamdullah; Tokgozoglu, Nedim; Salihoglu, Yavuz; Turan, Hasan; Iyibozkurt, Cem; Kolomuc, Tugba; et al.
Abstract : Objective: The purpose of this study was to investigate the outcomes and prognostic factors of metastasectomy in patients with metastatic ovarian tumors from extragenital primary sites. Materials and Methods: All patients with pathologically confirmed metastatic ovarian tumors between January 1997 and June 2015 were included in this study. A total of 131 patients were identified. The data were obtained from the patients' medical records. Clinicopathological features were evaluated by both univariate and multivariate analyses. Results: The primary sites were colorectal region (53.4%), stomach (26%), and breast (13%). Preoperative serum CA 125 and CA 19-9 levels were elevated in 29.4% and 39.8% of the patients, respectively. Cytoreductive surgery was performed in 41.2% of the patients. Seventy-three (55.7%) patients had no residual disease after surgery. Sixty-six (49.6%) patients had combined metastases at the time of the surgery to sites including the liver, pancreas, lung, bone, lymph nodes, bladder, or the intestine. With a median follow-up of 33 months, the median survival time was 22 months. The estimated 5-year survival probability is 0.26. On univariate analysis, primary cancer site, combined metastasis outside the ovaries, residual disease, preoperative serum CA 125 and CA 19-9 levels, and histologic type were significant parameters for overall survival. Furthermore, residual disease, preoperative serum CA 19-9 level, and primary cancer site were found to be independent prognostic factors on multivariate analysis. Conclusions: The most common primary sites for ovarian metastasis are gastrointestinal tract. Metastasectomy may have beneficial effects on survival, especially if the residual disease is less than 5 mm. Prospective studies warranted to evaluate the value of metastasectomy in patients with ovarian metastasis.